Peningkatan Kemampuan membaca Al Qur’an melalui Pembelajaran Tajwid Santri TPQ - Nida Nur Afia, Elfin; Faizah, Afidatul; Khoiriyah, Binti; Narti; Syarofah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
One aspect of reading the Al-Quran by Santri is their understanding of the science of recitation. Get to know the applicable laws of scientific reading. The standards for reading the Koran are known as tajwid, which includes the laws of reading nun sukun and tanwin, mim sukun, and the properties of letters. The science of tajwid is the science of reading the Koran correctly. Includes generating the sound of letters from their original position (makhraj), based on the nature of the sound (nature), understanding the implications of the properties of letters, and understanding when to stop reading (waqaf) and continue reading (ibtida). Fardu kifayah is a statutory regulation that regulates the study of the science of recitation but can be applied. Several problems researchers found during their research at TPQ Darussalam Dusun Tegalrejo, some of which were related to understanding recitation learning. Researchers found that the lack of experience of some Santri reading the Al-Quran had an impact on their capacity to read the Al-Quran. Participatory Action Research, or PAR, is the methodology that will be applied in this research. The aim of this research paradigm, known as Participatory Action Research, is to teach recitation knowledge to students to improve their ability to read the Al-Quran.